Late urinary toxicity modeling after stereotactic body radiotherapy (SBRT) in the definitive treatment of localized prostate cancer. (2nd January 2016) - Kole, Thomas P.; Tong, Michael; Wu, Binbin; Lei, Siyuan; Obayomi-Davies, Olusola; Chen, Leonard N.; Suy, Simeng; Dritschilo, Anatoly; Yorke, Ellen; Collins, Sean P.
Abstract : Background. Late urinary symptom flare has been shown to occur in a small subset of men treated with ultra- hypofractionated stereotactic body radiotherapy (SBRT) for prostate cancer. The purpose of this study was to use normal tissue complication probability modeling in an effort to derive SBRT specific dosimetric predictor's of late urinary flare. Material and methods. Two hundred and sixteen men were treated for localized prostate cancer using ultra- hypofractionated SBRT. A dose of 35–36.25 Gy in 5 fractions was delivered to the prostate and proximal seminal vesicles. Functional surveys were conducted before and after treatment to assess late toxicity. Phenomenologic NTCP models were fit to bladder DVHs and late urinary flare outcomes using maximum likelihood estimation. Results. Twenty-nine patients experienced late urinary flare within two years of completion of treatment. Fitting of bladder DVH data to a Lyman NTCP model resulted in parameter estimates of m, TD50, and n of 0.19 (0–0.47), 38.7 Gy (31.1–46.4), and 0.13 (-0.14–0.41), respectively. Subsequent fit to a hottest volume probit model revealed a significant association of late urinary flare with dose to the hottest 12.7% of bladder volume. Multivariate analysis resulted in a final model that included patient age and hottest volume probit model predictions. Kaplan-Meier analysis demonstrated a two-year urinary flare free survival of 95.7% in patients 65 years or older with a bladder D12.7% of 33.5 Gy or less, compared to 74.5% in patients meeting none of these criteria. Conclusion. NTCP modeling of late urinary flare after ultra-hypofractionated prostate SBRT demonstrates a relatively small volume effect for dose to the bladder, suggesting that reduction of volume receiving elevated dose will result in decreased incidence of late urinary toxicity. Future studies will be needed to examine the impact of dose to other potential sources of late genitourinary toxicity.